SISTEM PAKAR UNTUK MENDIAGNOSA KERUSAKAN PERANGKAT TELEVISI MENGGUNAKAN METODE BACKWARD CHAINING - Deny Wiria Nugraha (Jurnal Informatika, 2015)
This study aims to design and build an expert system that can diagnose damage to the television set based on the type and characteristics of the damage by using backward chaining method. The expert system in this study has been designed and built using the backward chaining method. It starts by proving the preliminary conclusions based on direct observations of users of the damage type to the television set that will be repaired, and the results show the facts and the rules appropriate to the type and characteristics of the damage to the television set. The expert system was proved capable of receiving, storing, and transferring knowledge from experts or repair technicians of the damage to the television set according to the type and characteristics of the actual damage to the television set. This expert system also proved to be able to function properly to diagnose problem of the television set based on the type and characteristics of the damage.